Poland Syndrome with Atypical Malformations Associated to a de novo 1.5 Mb Xp22.31 Duplication - Massimino, Carmela R.; Smilari, Pierluigi; Greco, Filippo; Marino, Silvia; Vecchio, Davide; Bartuli, Andrea; Parisi, Pasquale; Cho, Sung Y.; Pavone, Piero (Neuropediatrics, 2020)
Poland's syndrome (PS; OMIM 173800) is a rare congenital syndrome which consists of absence or hypoplasia of the pectoralis muscle. Other features can be variably associated, including rib defects. On the affected side other features (such as of breast and nipple anomalies, lack of subcutaneous tissue and skin annexes, hand anomalies, visceral, and vertebral malformation) have been variably documented. To date, association of PS with central nervous system malformation has been rarely reported remaining poorly understood and characterized. We report a left-sided PS patient carrying a de novo 1.5 Mb Xp22.31 duplication diagnosed in addiction to strabismus, optic nerves and chiasm hypoplasia, corpus callosum abnormalities, ectopic neurohypophysis, pyelic ectasia, and neurodevelopmental delay. Since, to our knowledge, this features' association has not been previously reported, we argue that this case may contribute to further widening of the variability of PS phenotype.
Keywords: Poland's syndrome; hypoplasic optic nerve; CNS involvement